Puding Labu Kuning sebagai Alternatif Makanan Fungsional dalam Pencegahan Stunting pada Balita di Desa Ajung Kalisat - Imam Baidowi; Ayu Puspitasari; Mailindza Sofia; Risha Tyas Septa; Ismatul Hasanah; Jamila Jamila; Maulana Adiwangsa; Rafi Lutfansyah Fakhrezi; Luluk Atul Fitriyah; Berlian Isni Azizah; Yogi Enggal Alfian fahrezi; Haiqul Umam; Intan Permatasari; Galang Athillah A.; Abdul Wakil; Ade Irma Novianti (Jurnal Kemitraan Masyarakat, 2024)
Stunting is a condition of impaired growth in children under five caused by chronic malnutrition and recurrent infections, which impacts the physical and cognitive development of the child. Ajung Kalisat Village has a relatively high prevalence of stunting, necessitating effective interventions to prevent this condition. This study aims to evaluate the potential of pumpkin pudding as an alternative functional food in the prevention of stunting in children under five in Ajung Kalisat Village. Pumpkin was chosen due to its high nutritional content, such as vitamin A, fiber, and antioxidants, which are beneficial for children's growth and development. The research method involved a trial of giving pumpkin pudding to children under five over a specific period and evaluating its impact on their nutritional status and growth. The results of the study showed that the consumption of pumpkin pudding significantly improved the nutritional status of children under five and has the potential to prevent stunting. Therefore, pumpkin pudding can be considered an effective alternative functional food in efforts to prevent stunting in the community.